ESTETIKA FASAD PADA BANGUNAN KOLONIAL GEDUNG SATE BANDUNG - Nurfradila; Rahayu, Tuntun (Jurnal Ilmiah Arjouna: Architecture and Environment Journal of Krisnadwipayana, 2020)
The facade is a natural building, front or outside. To judge the facade is a very subjective matter. Butdesigning for the public also means having the right way of doing it. The face of the building, window displaysand stage background are also part of the facade for the design. By using aesthetic theory we can create afacade with a visual that is appropriate for the public and analyze it. The facade is an aesthetic balance. Thecolonial building facade is a facade with a distinctive character that has good visuals. This research willexamine the uniqueness of the colonial facade building using aesthetic principles theory. The balance on thecolonial building facade will be an example of how a good facade should be, a facade with aesthetic unity.